Peripheral nerve regeneration following injury is altered in mice lacking P2X7 receptor. (22nd October 2020) - Magnaghi, Valerio; Martin, Sarah; Smith, Patrick; Allen, Luke; Conte, Vincenzo; Reid, Adam J.; Faroni, Alessandro
Abstract: Peripheral nerve injuries are debilitating, and current clinical management is limited to surgical intervention, which often leads to poor functional outcomes. Development of pharmacological interventions aimed at enhancing regeneration may improve this. One potential pharmacological target is the P2X purinergic receptor 7 (P2X7R) expressed in Schwann cells, which is known to play a role during the development of the peripheral nerves. Herein, we analysed differences in regeneration between genetically engineered P2X7 knockout mice and wild‐type controls, using in vivo and ex vivo models of peripheral nerve regeneration. We have found that the speed of axonal regeneration is unaltered in P2X7 knockout mice, nevertheless regenerated P2X7 knockout nerves are morphologically different to wild‐type nerves following transection and immediate repair. Indeed, the detailed morphometric analysis at 4 and 8 weeks after injury showed evidence of delayed remyelination in P2X7 knockout mice, compared to the wild‐type controls. Furthermore, the Wallerian degeneration phase was unaltered between the two experimental groups. We also analysed gene expression changes in the dorsal root ganglia neurones as a result of the peripheral nerve injury, and found changes in pathways related to pain, inflammation and cell death. We conclude that P2X7 receptors in Schwann cells may be a putative pharmacological target to control cell fate following injury, thus enhancing nerve re‐myelination. Abstract : Following injury, Schwann cells de‐differentiate into a "repair" phenotype which drives nerve regeneration. After repair, Schwann cells re‐differentiate into myelinating or non‐myelinating phenotype. Herein, we showed that Wallerian degeneration and nerve regeneration speed are unaltered in mice lacking P2X7R, compared to controls. Nevertheless, the lack of P2X7 receptors hinders the re‐myelinating potential of repair Schwann cells resulting in delayed and less effective remyelination.